The Terubuk Fish in Bengkalis 19th to 20th Century: A Study of Animal History - Syahrian, Windi; Rahmat, Syahrul (Journal of Philology and Historical Review, 2023)
Terubuk fish were an important part of the life of the Bengkalis people in the past, both from an economic and cultural perspective. The high selling price in the market made terubuk a target for fishermen in the area and even involved local and colonial governments. This article examines the history of the catching and trading of terubuk from time to time, as well as the involvement of terubuk in historical dynamics in Bengkalis in the 19th to 20th centuries. This research is historical research which consists of four stages, namely heuristics, source criticism, interpretation and historiography. The results of the research were then analyzed using an animal history approach, in which, according to Rees, animals are agents who have the capacity to contribute to history. As a result of the research, Ikan Terubuk is an agent who plays an important role in the dynamics of trade and cultural history in Bengkalis. From the trade aspect, terubuk is a commodity with high economic value and has also been one of the export commodities in the past. Meanwhile, from the cultural aspect, the idea of ikan terubuk is manifested in the form of tradition through the semah terubuk ceremony and the creation of syair ikan terubuk.